2015
DOI: 10.1016/j.brainres.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

The evolving roles of pericyte in early brain injury after subarachnoid hemorrhage

Abstract: Despite accumulated understanding on the mechanisms of early brain injury and improved management of subarachnoid hemorrhage(SAH), it is still one of the serious and refractory health problems around the world. Traditionally, pericyte served as capillary contraction handler, is recently considered as the main participant of microcirculation regulation in SAH pathophysiology. However, accumulate evidences indicate pericyte is much more than we already know. Therefore, we briefly review the characteristics, regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 174 publications
(190 reference statements)
2
20
0
1
Order By: Relevance
“…As microvessels lack smooth muscle, blood flow is frequently assumed to be regulated by precapillary arterioles. However, the majority (65%) of adrenergic innervation of central nervous system (CNS) blood vessels terminates near microvessels rather than arterioles, and in the muscle and brain a dilatory signal propagates from vessels near metabolically active cells to precapillary arterioles, suggesting that blood flow control is initiated in microvessels ( 4 , 5 , 7 ). Pericytes in CNS microvessels contain contractile proteins and can initiate such signaling ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As microvessels lack smooth muscle, blood flow is frequently assumed to be regulated by precapillary arterioles. However, the majority (65%) of adrenergic innervation of central nervous system (CNS) blood vessels terminates near microvessels rather than arterioles, and in the muscle and brain a dilatory signal propagates from vessels near metabolically active cells to precapillary arterioles, suggesting that blood flow control is initiated in microvessels ( 4 , 5 , 7 ). Pericytes in CNS microvessels contain contractile proteins and can initiate such signaling ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…An explanation for these results could be that cerebral microcirculation and its regulatory mechanisms are directly affected by SAH ( 4 ), particularly pericytes, the primary cell type controlling microcirculation in brain parenchyma ( 5 ). A number of studies have addressed the role of microcirculatory dysfunction during SAH, where arteriolar constriction is typically observed ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Germinal matrix hemorrhage (GMH) is a common cerebrovascular event that affects up to 20% of premature infants, and leads to severe long-term neurological and cognitive deficits, including cerebral palsy and mental retardation (Ballabh, 2014). After the hemorrhage occurs, the damage of brain tissue is amplified by the activation of inflammatory cascades, which are responsible for the further neurodegeneration (Brown and Neher, 2010; Chen et al, 2015; Tao et al, 2016; Zhou et al, 2014). Given the extended inflammation-induced tissue destruction, the suppression of inflammatory response could be a particularly important intervention to limit GMH-induced brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…In our experiments, we knocked out retention motif of PDGF-B, which is the binding site of PDGF-B with the extracellular matrix [16]. Previous studies demonstrated that PDGF-B ret/ret mice suffered cerebral vascular dysfunction by pericyte recruitment deficiency and subsequent breach on the blood-brain barrier after SAH [4,[17][18][19][20]. Similarly, the pericytes were covered with 26-40% microvessels in mature lungs [21], which might also be regulated by PDGF-B in the pathophysiological progression after SAH to cause pulmonary edema, previously considered to be neurogenic [22].…”
Section: Discussionmentioning
confidence: 99%